Pengaruh Pengetahuan Keselamatan dan Kesehatan Kerja dan Sikap terhadap Hasil Belajar Siswa - Mar'i Muhamad; Ahyanuardi Ahyanuardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
The goal of this study was to determine the relationship between occupational safety and health knowledge and attitudes toward student learning outcomes. This study employs quantitative research methods, which means that all information or data is represented numerically and that the analysis is based on statistical analysis. The research method used is causal associative research. The research instrument employs a questionnaire that has been validated by an occupational safety and health lecturer and is tested before being distributed to Electrical Power Installation Engineering students. Following the trial, the questionnaire is tested for validity and reliability. A Likert scale is used to evaluate research instruments. In this study, data was analyzed using a simple correlation test as well as multiple correlation tests. To determine the partial relationship between the independent and dependent variables, a simple correlation test is used. The multiple correlation test is used to determine the relationship between the independent variables and the dependent variable at the same time. The findings revealed that (1) occupational safety and health knowledge has a weak relationship with student learning outcomes. (2) There is a weak relationship between attitudes and student learning outcomes. (3) Occupational safety and health knowledge and attitudes have a weak relationship with student learning outcomes.